Modafinil Reduces Neuronal Pyroptosis and Cognitive Decline After Sleep Deprivation - Xiong, Xiangyang; Zuo, Yan; Cheng, Lu; Yin, Zhenyu; Hu, Tianpeng; Guo, Mengtian; Han, Zhaoli; Ge, Xintong; Li, Wenzhu; Wang, Yan; Wang, Dong; Wang, Conglin; et al. (Frontiers in Neuroscience, 2022)
Sleep deprivation(SD) induces systemic inflammation that promotes neuronal pyroptosis. The purpose of this study was to investigate the effect of an antioxidant modafinil on neuronal pyroptosis and cognitive decline following SD. Using a mouse model of SD, we found that modafinil improved learning and memory，reduced proinflammatory factor (IL-1β,TNF-α,IL-6) production and increased the expression of an anti-inflammatory factors (IL-10). Modafinil treatment attenuated inflammasome activity and reduced neuronal pyroptosis involving the NLRP3/NLRP1/NLRC4-Caspase-1-IL-1β pathway. In addition, modafinil induced an upregulation of brain-derived neurotrophic factor (BDNF) and synaptic activity. These results suggest that modafinil reduces neuronal pyroptosis and cognitive decline following SD.These effects should be further investigated in future studies to benefit patients with sleep disorders.